PERAN BIMBINGAN PENYULUHAN UNIT BINTIBMAS SATUAN BINMAS DALAM MENCEGAH PENYALAHGUNAAN NARKOBA: PERAN BIMBINGAN PENYULUHAN UNIT BINTIBMAS SATUAN BINMAS DALAM MENCEGAH PENYALAHGUNAAN NARKOBA - BAGAS DWI AKBAR (Police Studies Review, 2020)
ABSTRACT The purpose of this study was to counseling guidance for Bintibmas unit of the Binmas unit to prevent the drug abuse in Bandung’s Polrestabes law region. Therefore, This study is conducted to know a general picture of drugs abuse in the city of Bandung, the implementation of counseling guidance, factors that influence and how to increase the role of guidance in efforts to prevent drug abuse. This research discusses by using concept of counseling guidance, the Binmas Unit concept, the concept of guidance management, the concept of misapropriation drugs as well as role theory, management theory and communication theory. The research aproach uses qualitative by using descriptive analysis methods and data collection through observation, interviews, and document review. The results of research found that the number of drug abuse in Bandung region is still high and has been increasing over the past three years. The role of conseling guidance that has been given by the Bintibmas Unit of the Binmas unit Bandung’s Polrestabes has not been maximized because it has not applied the method in accordance with Perkap number 21 of 2007 and found some obstacles. These obstacles include the lack of personnel, the quality of human resources is not evenly distributed, lack of quality of counseling material. Personnel communication support must be increased by the role of the Bintibmas Unit in effort to prevent drug abuse. From the research findings, the researcher recommend to Bintibmas Unit of the Binmas unit in Bandung’s Polrestabes for increasing the personnel number and giving a dikjur, increasing the amount of the budget to support impromptu activities, add counseling props to make counseling more interesting, invite drug’s former users to find out about the needs problem drugs and make no-drug movements that invite all of society with intensified time more intensity.